Digital Governance and its Role in Activating Competition and Preventing Monopoly in Iraq (International Journal of Financial, Administrative and Economic Sciences, 2026)
Digital government is receiving significant attention due to its effectiveness and diverse uses for transformation, sustainability, and innovation in the digital age. It is the reinvention of businesses through new methods for integrating and integrating information and providing access to it via websites. It is a new and advanced approach, providing a unified strategy and effective leadership to guide and motivate the use of technology to raise performance and activate the role of oversight over processes and their outcomes. It regulates the digital transformation process, employment policies, competition, and performance, acting as a pre-sensor for decision-making and adopting appropriate solutions and treatments.Digital governance and economic intelligence play a prominent role in stimulating competition in trade and production, stimulating small and medium-sized enterprises, reducing corruption, red tape, and tax evasion, and in activating the procedures of the Standardization and Quality Control Authority to enhance competition, protect emerging companies (protectionism), and limit monopoly. Therefore, it is necessary to prepare for the requirements of digital transformation to regulate competition, prevent monopoly, develop active sectors, and create an environment and climate conducive to foreign investment and development. Digital governance enables the transition to a knowledge economy and begins with the fundamental foundations of sustainable development.
Keywords: Digital Governance; Competition; Antitrust; Sustainable Development